Pengaruh Ac-Di –Sol Terhadap Karakteristik Fisik dan Laju Disolusi Orally Disintegrating Tablet Piroksikam dengan Metode Cetak Langsung - Setyawan, Dwi; Widjaja, Bambang; Sayekti, Indah (Majalah Ilmu Kefarmasian, 2010)
Orally Disintegrating Tablet (ODT) or Fast Release Tablet is solid dosage form which disintegrated rapidly in mouth and its residue easy to swallowed. This research observed the influence of Ac-Di-Sol concentration as disintegrant on physical characteristics and dissolution rate of piroxicam orally disintegrating tablet which were prepared by direct compression. Ac-Di-Sol was used in concentration of 1%, 3% and 5%, and 0% as control. The powder blend was pressed into tablet by hydraulic press with a pressure of 1 ton and diameter of 8 mm and its hardness, friability, disintegration time and dissolution rate were examined. The results showed that the increasing of Ac-Di-Sol concentration would increase hardness, disintegration time, dissolution rate and decrease friability of the tablet. From statistical analysis (µ =0,05), it was showed that there was significant difference among formulas on the hardness, friability, disintegration time and dissolution rate. The hardness of piroxicam Orally Disintegrating Tablet of all formulas were between 0.99 - 2.77 kP, friability were between 3.45 – 1.35%, disintegration time were between 223.67 – 20,0 sec and drug released at 45 minutes were between 32.71 – 96.25%. From this research, it could be concluded that formula with 3% concentration of Ac- Di-Sol give the most desirable output, even though there was a problem with the friability.